MANAJEMEN LAYANAN BIMBINGAN KONSELING DALAM UPAYA MENINGKATKAN MUTU BELAJAR DI SMPN 2 WONOSARI GUNUNGKIDUL TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This study is to know The Management of Guidance Counseling Service to enhance Learning Quality at SMP Negeri 2 Wonosari and to understand the meaning of Counseling Guidance Service in enhancing learning quality at SMP Negeri 2 Wonosari. This study applies qualitative approach. This study is used to examine the object in natural condition, the writer is as key instrument. The result of qualitative research emphasizes to meaning rather than generalization. This study is done at SMP Negeri 2 Wonosari in Gunungkidul regency. The techniques of data collection are direct observation, interview and documentation. The conclusion of this study are : (1) The Management of Guidance Counseling Service consists of program planning, organizing, program implementation, evaluation, and supervision control. (2) Program Planning is started by need assessment by considering to students’ problems which often raise, they are learning problem and emotion problem. (3 ) Organizing relates to job description which involved in Guidance Counseling Service activities proportionally, in order that the organization runs effectively and efficiently. (4) Program implementation is the core of Guidance Counseling Service. Counselor is demanded professional.(5) Evaluation activity, supervision control are established in order to reach endless qualified service(6) Counseling Guidance Service at SMP Negeri 2 Wonosari runs relatively well. (7) Guidance Counseling Service has contribution and real role in enhancing students’ learning quality. (8) The real and strategic contribution of Guidance Counseling Service, finally have contribution in enhancing learning quality.